2021
DOI: 10.37992/2021.1202.048
|View full text |Cite
|
Sign up to set email alerts
|

Gene action, combining ability and standard heterosis for seed cotton yield and fibre quality components in upland cotton

Abstract: Twelve parental genotypes and twenty F 1 hybrids developed in a Line x Tester fashion were used in the present study to estimate gene action, combining ability and standard heterosis for eleven quantitative and five quality traits in cotton. All the traits studied exhibited greater SCA variance than GCA except days to fifty per cent flowering suggesting that these traits are controlled by dominant gene action. Among the parents used, SVPR 2 and TSH 325 were detected with higher general combining ability for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The highest mid parent and better parent value was observed for the trait upper half mean length in the cross TCH 1199 × RHC 1409 (19.37%, 15.16%). The cross CO 14 × GTHV 323 had a maximum mid parent value (10.38%) for the elongation length and Monicashree et al (2017) and Khokhar et al (2018) also confirmed the non-additive gene action that was appeared to be dominant in the traits viz., the number of sympodia per plant, the number of bolls per plant, boll weight and seed cotton yield per plant as suggested by Gnanasekaran et al (2021). Non-additive gene action results due to the lack of association between per se performance and the gca effects of parents i.e., either having values of high mean with low gca effects or vice versa.…”
Section: Table1 Analysis Of Variance For Cotton Yield and Quality Tra...mentioning
confidence: 99%
“…The highest mid parent and better parent value was observed for the trait upper half mean length in the cross TCH 1199 × RHC 1409 (19.37%, 15.16%). The cross CO 14 × GTHV 323 had a maximum mid parent value (10.38%) for the elongation length and Monicashree et al (2017) and Khokhar et al (2018) also confirmed the non-additive gene action that was appeared to be dominant in the traits viz., the number of sympodia per plant, the number of bolls per plant, boll weight and seed cotton yield per plant as suggested by Gnanasekaran et al (2021). Non-additive gene action results due to the lack of association between per se performance and the gca effects of parents i.e., either having values of high mean with low gca effects or vice versa.…”
Section: Table1 Analysis Of Variance For Cotton Yield and Quality Tra...mentioning
confidence: 99%
“…Previous studies have shown that parents with good per se performance might not produce useful progenies when used in hybridization. The selection of appropriate parents for the improvement of elite hybrid depends on the selection of parents based on combining ability (Gnanasekaran and Thiyagu, 2021). Combining ability also gives information about the nature of gene action responsible for the inheritance of quantitative traits.…”
Section: Introductionmentioning
confidence: 99%